Traditional Dietary Knowledge of a Marginal Hill Community in the Central Himalaya: Implications for Food, Nutrition, and Medicinal Security - Ojha, S. N.; Anand, Aryan; Sundriyal, R. C.; Arya, Deepshikha (Frontiers in Pharmacology, 2022)
Himalayan communities illustrate a rich agriculture-medicine use system that not only provides adequate dietary diversity and nutrition but also delivers therapeutic security. This paper explores the food-medicine interface as observed by the marginal hill communities in the central Himalaya with an aim to assess traditional agriculture and food plants with relation to dietary diversity, nutritional, and medicinal values based on comprehensive research. A total of 445 respondents were interviewed to obtain data on food intakes using dietary recall methods and dietary diversity indices (DDI). The ethnomedical use of plant species was gathered from respondents as well as from various published works for respective species. Nutritional parameters were collected from the Indian Food Composition Table (IFCT) developed by ICMR, India to analyze the average nutritional intake. The traditional food system achieves the dietary and nutritional needs of the community within the standard norms. The average household dietary diversity of 7.45, 7.34, and 8.39 in summer, monsoon, and winter seasons, respectively, sustain 79%, 74%, and 93% of energy requirements in respective seasons. The average food consumption score(FCS) was 73.46 and all the food exhibited rich phytochemicals such as amino acids, alkaloids, carotenoids, flavonoids, glycosides, phenolic acids, etc. These plants also provided effective treatments against several ailments and illnesses, such as cardiovascular diseases, diabetics, gastro-intestinal issues, inflammation, etc. The indigenous cuisines also have significant food and medicinal values. Considering that the community comprised a significant knowledge of food systems with their nutritional and therapeutic utility there is a need to protect and document this indigenous knowledge. Also, most of the crops are still under cultivation, there is a need to create more awareness about the nutritional and therapeutic value of the system so that it could be retained intact and continued. The implications of this research are of both academic importance and practical significance to ensure food-medicine security and avoid malnutrition among rural communities. It is expected that the study would lead to renewed thinking and policy attention on traditional agriculture for its role in food and nutritional security that may lead to a sustainable food supply system.